The discovery of late Triassic mylonitic granite and geologic significance in the middle Gangdese batholiths, southern Tibet. (February 2017) - Ma, Shiwei; Meng, Yuanku; Xu, Zhiqin; Liu, Xiaojia
Highlights: Discovery of late Triassic mylonitic granite in the Gangdese magmatic belt, southern Tibet. The late Triassic mylonitic granite were generated in an active setting with a multiple islands. Mantle-derived magmas played an important role in its origin. Zircon Lu-Hf data indicate growth in southern Tibet during late Triassic. Abstract: The Gangdese magmatic belt, located in the southern margin of the Lhasa terrain and carrying significant copper poly-metallic mineralization, preserves important information related to the tectonics associated with the Neo-Tethys Ocean subduction, Indian-Asian collision and the crustal growth of southern Tibet. Here, we investigated the Namling batholiths in the central domain of the Gangdese magmatic belt and report for the first time the occurrence of late Triassic mylonitic granite, and present its petrologic, zircon U-Pb-Hf isotopes and the whole-rock chemistry dataset. Zircon LA-ICP-MS U-Pb dating from three mylonitic granitic samples yields crystallization ages of 209.4 ± 1.1 Ma, 206.7 ± 1.1 Ma and 212 ± 1.1Ma, indicating a late Triassic magmatic event in the Gangdese magmatic belt. Geochemically, the mylonitic granite exhibits magnesian genesis and calcic and calc-alkalic features. The depletions of Nb, Ta and Ti and enrichments of LREEs together suggest that the magmas from which these rocks crystallized were generated in an active continental margin. Besides, all the analyzed samples also demonstrate highly positive εHf (t) values of 8.95–12.91 (mean value 10.84), corresponding to single stage model ages (t DM1 ) in the range of 326 Ma–486 Ma (mean 414 Ma), attesting to crustal growth in southern Lhasa terrain. The mylonitic pluton are likely sourced from partial melting of the lower crustal components (amphibolite or basaltic stuff) that was heated and metasomatized by underplating basaltic magmas, and subsequently might undergo fractional crystallization and upper sediments contamination during parental magmas ascent. In light of the distribution of the early Mesozoic magmatic events and robust sedimentary evidence together suggest that the northward subduction of the Neo-Tethys oceanic crust beneath the Lhasa terrain should commence prior to late Triassic (∼210 Ma).